2022
DOI: 10.1021/acs.chemmater.1c03072
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Supraballs of Mesoporous Silica Nanoparticles as Bioresorbable Adhesives for Hydrogels

Abstract: The adsorption of polymers at the surface of mesoporous silica nanoparticles (MSNs) has been shown to provide a versatile way to create adhesion between hydrogels or biological tissues. Nevertheless, above a critical number of deposited nanoparticles, thick multilayers accumulate at the interface and the adhesion strength decreases as cracks easily propagate between weakly cohesive polymer-free nanoparticles. In order to suppress this limitation, we prepared spherical aggregates by spray drying during which MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…44 Meanwhile, SNs are able to serve as the physical cross-link points of the hydrogels to increase the polymeric cross-linking density, thus improving the mechanical robustness upon deformation. 45,46 For example, Meng et al 47 presented a hysteresis-free hydrogel by hyperbranched silica nanoparticles acting as the dominant cross-links to exhibit superior elastic behavior, virtually free of mechanical hysteresis even after 5000 cyclic loadings. Hence, considering these unique advantages, we chose SNs as the nanoreinforced materials for the fabrication of excellent mechanical properties hydrogels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Meanwhile, SNs are able to serve as the physical cross-link points of the hydrogels to increase the polymeric cross-linking density, thus improving the mechanical robustness upon deformation. 45,46 For example, Meng et al 47 presented a hysteresis-free hydrogel by hyperbranched silica nanoparticles acting as the dominant cross-links to exhibit superior elastic behavior, virtually free of mechanical hysteresis even after 5000 cyclic loadings. Hence, considering these unique advantages, we chose SNs as the nanoreinforced materials for the fabrication of excellent mechanical properties hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, silica nanoparticles (SNs) are one of promising nanofillers for preparing tough nanocomposite hydrogels, due to their uniform structure, high adsorption capacity, and abundance of surface hydroxyl groups . Meanwhile, SNs are able to serve as the physical cross-link points of the hydrogels to increase the polymeric cross-linking density, thus improving the mechanical robustness upon deformation. , For example, Meng et al . presented a hysteresis-free hydrogel by hyperbranched silica nanoparticles acting as the dominant cross-links to exhibit superior elastic behavior, virtually free of mechanical hysteresis even after 5000 cyclic loadings.…”
Section: Introductionmentioning
confidence: 99%
“…Hybridization is one of most general strengthening strategies in material science. Over the past decade, various kinds of organic or inorganic reinforcing agents with shape ranging from 0D (e.g., silica nanoparticle, , hydroxyapatite nanoparticle , ) to 1D (e.g., CNF, ,, CNC, , , carbon nanotube , ) to 2D (e.g., graphene oxide, , MXene , ) materials, as well as polymer chains, , have been introduced to enhance the mechanical strength of cellulose-based hydrogel. For example, Deng et al demonstrated that addition of 5 wt % rectorite can significantly improve the maximum compressive stress of cellulose/chitosan hydrogel to 5.65 MPa .…”
Section: Properties and Performancementioning
confidence: 99%
“…Based on their simulation results, Baik et al . claimed in 2022 [30] that when two hydrogels are adhered using a high-concentration nanoparticulate adhesive, resulting in the accumulation of a thick multilayer of nanoparticles between them, they can be easily separated via the propagation of a crack formed in the nanoparticle layer (i.e . , owing to cohesive failure of the adhesive) because of weak interparticle forces.…”
Section: Inorganic Solid-state Adhesivesmentioning
confidence: 99%
“…Baik et al . achieved this by fabricating micron-sized spherical aggregates of nanoparticles, which led to an approximately 200 % increase in the adhesion energy compared with that of non-aggregated nanoparticles [30] . Another way to improve the adhesion strength (i.e .…”
Section: Inorganic Solid-state Adhesivesmentioning
confidence: 99%